Pengaruh Custemer Value, Custemer Relationship Management, serta Custemer Experience terhadap Custemer Loyalty Debitur Lending yang terdapat di Bank OCBC NISP Cabang Purwakarta - Purnomo, Eddy; Hartelina, Hartelina; Nadeak, Banuara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of customer value on customer loyalty, determine and analyze the influence of customer relationship management on customer loyalty, and determine and analyze the influence of customer experience on customer loyalty for lending debtors. The method used in this research is descriptive verification. With this type of associative research. The population used in this research is Bank OCBC NISP Purwakarta branch customers. The results of this research show that customer value influences the loyalty of lending debtors. Customer relationships influence loyal customers of lending debtors, customer experience has an influence on customer loyalty of lending debtors at OCBC NISP bank.